2022
DOI: 10.3390/app12031408
|View full text |Cite
|
Sign up to set email alerts
|

Members of the AP-1 Family of Transcription Factors Regulate the Expression of Gja1 in Mouse GC-1 Spermatogonial Cells

Abstract: Gap junctions, mainly formed by Gja1 (Connexin43), play an essential role in the regulation of proliferation and differentiation of spermatogonia in the testis. Regulation of the abundance of Gja1 in spermatogonia involves various processes, including gene transcription, mRNA maturation, protein synthesis, post-translational modifications, plasma membrane integration and protein degradation. However, gene expression of Gja1 is abnormally decreased in most testicular germ cell tumors. Hence, a better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(92 reference statements)
2
0
0
Order By: Relevance
“…As demonstrated by our results, the addition of SOX4 either on its own or in cooperation with AP-1 factors had regulatory activity at the promoters of known labour associated genes; however, SOX4 did not regulate the Gja1 promoter. This result was surprising at first because Ghouili et al showed SOX and JUN factors can transactivate their targets together; however, our result is consistent with Najih et al who demonstrated the dispensable role of SOX4 on Gja1 promoter activity in spermatogonia GC-1 cells (16,29).…”
Section: Discussionsupporting
confidence: 85%
“…As demonstrated by our results, the addition of SOX4 either on its own or in cooperation with AP-1 factors had regulatory activity at the promoters of known labour associated genes; however, SOX4 did not regulate the Gja1 promoter. This result was surprising at first because Ghouili et al showed SOX and JUN factors can transactivate their targets together; however, our result is consistent with Najih et al who demonstrated the dispensable role of SOX4 on Gja1 promoter activity in spermatogonia GC-1 cells (16,29).…”
Section: Discussionsupporting
confidence: 85%
“…As demonstrated by our results, the addition of SOX4 either on its own or in cooperation with AP-1 factors had regulatory activity at the promoters of known labour associated genes; however, SOX4 did not regulate the Gja1 promoter. This result was surprising at first because Ghouili et al showed SOX and JUN factors can transactivate their targets together; however, our result is consistent with Najih et al who demonstrated the dispensable role of SOX4 on Gja1 promoter activity in spermatogonia GC-1 cells [ 16 , 29 ]. Contrarily, SOX4 demonstrated a notable activating effect on the Fos promoter, but only in a cellular context that lacks FOSL2 protein and overexpresses JUND.…”
Section: Discussionsupporting
confidence: 84%